Comparison of Reliability of Tap Test and Shake Test for Determination of Fetal Lung Maturity - Bajracharya, S (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: To compare the reliability of tap test and shake test for determination of fetal lung maturity in pregnant women between 28 weeks and 36 completed week’s gestation either with preterm prelabour rupture of membrane or preterm labour. Methods: Amniotic fluid samples from vaginal pool were obtained from one hundred pregnant women who met the inclusion criteria. Both tap test and shake test were performed in each sample. All deliveries occurred within 72 hours of collection of amniotic fluid. The results of the tests were compared with the incidence of neonatal respiratory distress syndrome. Results: Out of 100 tests performed, tap test predicted 17% as immature and 83% as mature and shake test predicted 51% as immature and 49% as mature. Among 100 newborns, 9 (9%) were found to be true immature as they developed respiratory distress syndrome. The sensitivity, specificity, predictive value for fetal lung immaturity and maturity by tap test was 88.9%, 90.1%, 47.1% and 98.8% respectively and the sensitivity, specificity, predictive value for fetal lung immaturity and maturity by shake test was 100%, 53.8%,17.6% and 100% respectively. Conclusions: In view of very low specificity and predictive value for fetal lung immaturity by shake test compared to that by tap test and lower sensitivity of the tap test than the shake test, neither of the tests is reliable than the other and these two tests can not replace each other DOI: http://www.dx.doi.org/10.3126/njog.v7i2.11141 Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 2 / Issue 14 / July-Dec, 2012 / 36-39